2004
DOI: 10.1038/sj.npp.1300591
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Clozapine on Extracellular Dopamine Levels in the Shell Subregion of the Rat Nucleus Accumbens is Reversed Following Chronic Administration: Comparison with a Selective 5-HT2C Receptor Antagonist

Abstract: The clinical onset of both the therapeutic and side effects of antipsychotic drugs can take days/weeks to develop. Therefore, it is likely that adaptive changes in neurotransmission of key systems may only manifest upon chronic administration. Thus, using in vivo microdialysis we have evaluated the acute and chronic (21 days) effects of the atypical antipsychotic clozapine on nucleus accumbens (NAcc) dopamine (DA) output in the rat. Clozapine (10 mg/kg p.o.) produced an acute 60% increase in extracellular leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 45 publications
2
23
1
Order By: Relevance
“…Atypical antipsychotic drugs, including clozapine and olanzapine, can increase DA efflux in the NAc, although the magnitude of the effect is significantly smaller than that produced in the mPFC (Ichikawa et al, 2002c;Kuroki et al, 1999;Shilliam and Dawson, 2005). Shilliam and Dawson (2005) demonstrated that this increase was confined to the shell of the NAc and did not occur in the NAc core.…”
Section: Da Effluxmentioning
confidence: 99%
See 1 more Smart Citation
“…Atypical antipsychotic drugs, including clozapine and olanzapine, can increase DA efflux in the NAc, although the magnitude of the effect is significantly smaller than that produced in the mPFC (Ichikawa et al, 2002c;Kuroki et al, 1999;Shilliam and Dawson, 2005). Shilliam and Dawson (2005) demonstrated that this increase was confined to the shell of the NAc and did not occur in the NAc core.…”
Section: Da Effluxmentioning
confidence: 99%
“…Atypical antipsychotic drugs, including clozapine and olanzapine, can increase DA efflux in the NAc, although the magnitude of the effect is significantly smaller than that produced in the mPFC (Ichikawa et al, 2002c;Kuroki et al, 1999;Shilliam and Dawson, 2005). Shilliam and Dawson (2005) demonstrated that this increase was confined to the shell of the NAc and did not occur in the NAc core. We have previously shown that 5-HT 2C -receptor antagonism, in combination with D 2 -receptor antagonism, may contribute to the ability of these agents to enhance DA release in the NAc (Bonaccorso et al, 2002;Li et al, 2005).…”
Section: Da Effluxmentioning
confidence: 99%
“…Antagonism at 5-HT 2C receptors by several antipsychotics was also observed in vivo. Indeed, clozapine produces an increase in extracellular levels of DA in the nucleus accumbens [192,193], reverses the inhibition of accumbal DA release induced by the 5-HT 2C agonist RO 60-0175 [192] and blocks the hypolocomotion induced by the 5-HT 2C agonist mCPP [194].…”
Section: -Ht 2c Recptors and Schizophreniamentioning
confidence: 99%
“…However, the bias did not diminish the clozapine efficacy at the end of study, likely due to its more polyvalent, unique receptor pharmacology than other antipsychotic drugs 26 . The selective changes in neurotransmission produced by clozapine antipsychotic action were rather time-dependent than dose-dependent, which may be a reason of delayed therapeutic activity 27 and also the effectiveness of moderate to low doses in our study.…”
Section: Discussionmentioning
confidence: 78%